Rifampicin-resistant Mycobacterium tuberculosis and unsuccessful results from Xpert® MTB/Rif-Ultra assay in Amhara Region, Ethiopia - Gizeaddis Belay; Hailu Getachew; Tigist Birku; Aimro Tadese; Yosef Gashaw; Michael Getie; Tazeb Molla; Molalign Tarekegn; Daniel Mekonnen; Alemayehu Abate (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases, 2025)
Background: Tuberculosis, an infectious disease caused by Mycobacterium tuberculosis (Mtb), causes 10 million new infections and 1.3 million deaths annually. The treatment of TB is hampered by the increasing incidence rate of drug resistance associated with TB. To diagnose TB and identify drug-resistant TB cases, rapid molecular technologies such as Xpert MTB/RIF, Truenat MTB, MTB Plus, and MTB-RIF Dx tests are recommended by the World Health Organization (WHO) and rolled out globally. Xpert MTB/RIF-Ultra assay is the most widely used in developing countries like Ethiopia. However, this rapid technology has inherent limitations, such as error reports, invalid results, and no results collectively reported as unsuccessful tuberculosis results. The purpose of this study was to retrospectively evaluate the trend of rifampicin resistance and unsuccessful results in the Xpert MTB/RIF-Ultra assay facility of Northwest Ethiopia. Methods: Retrospective data archived in the Amhara Public Health Institute (APHI) TB laboratory from 2019 to 2024 were reviewed. Xpert MTB/RIF-Ultra software data were retrieved and transferred to Microsoft Excel. Then, it was checked for completeness, cleaned manually, and imported to Statistical Package for the Social Sciences (SPSS) version 25 software. The rate of mycobacterium tuberculosis (Mtb.) positives, multi-drug resistance tuberculosis (MDR-TB), and Unsuccessful results were analyzed from the total and year-wise. The final results were depicted using tables and different charts. Results: From June 30, 2019, to June 30, 2024, a total of 587,128 sputum samples were obtained from presumptive TB patients in 111 GeneXpert sites in the Amhara Region. Of these samples analyzed using Xpert MTB/RIF-Ultra, 6.17 % (36,212/587,128) were Mtb positive. Furthermore, the overall proportion of rifampicin resistance (RR) among Mtb-confirmed cases decreased to 3.03 % (1,096/36,212) and showed a downward trend from 4.62 % (184/3979) in 2020 to 2 % (176/8806) in 2024. The overall unsuccessful results (error, invalid & no result) were 6.48 %. The rate of unsuccessful results remained above the national target of < 5 % throughout the study periods. Conclusion and recommendation: The rate of Mtb and MDR-TB showed a decreasing trend in the last six years in Northwest Ethiopia. However, unsuccessful results remained above the national target. The cause of unsuccessful results should be investigated, and the Xpert MTB/RIF-Ultra-related quality assurance system must be enhanced to reduce the rate of Xpert MTB/RIF-Ultra unsuccessful results.